2021
DOI: 10.1523/jneurosci.2200-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Induces Light Aversion in Mice by an Inheritable Mechanism Independent of CGRP

Abstract: The contents do not represent the views of VA or the United States Government. We thank Michael Anderson and Kai Wang for help interpreting the inheritance pattern and Johannes Ledolter for help with statistical analysis..

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 103 publications
2
34
1
Order By: Relevance
“…We also showed this both in knockout mice without functional CGRP receptors and by antibody neutralization of CGRP. Our ndings are supported by data from another group using light aversion in mice as a surrogate for migraine-like photophobia to compare CGRP and PACAP38 (11). These ndings are important as PACAP38 is the only migraine trigger tested in our rodent model to bypass CGRP.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…We also showed this both in knockout mice without functional CGRP receptors and by antibody neutralization of CGRP. Our ndings are supported by data from another group using light aversion in mice as a surrogate for migraine-like photophobia to compare CGRP and PACAP38 (11). These ndings are important as PACAP38 is the only migraine trigger tested in our rodent model to bypass CGRP.…”
Section: Introductionsupporting
confidence: 75%
“…This contrasts with previous observations in mice sensitized by GTN and levcromakalim where CGRP antagonism was highly effective (22). Light aversion in mice as a surrogate for migraine-like photophobia was used to compare CGRP and PACAP38 (11). It showed that one-third of mice did not respond to PACAP38, which was not seen with CGRP.…”
Section: Pacap38 Signaling Pathways Are Distinctcontrasting
confidence: 69%
See 1 more Smart Citation
“…TRPC5 inhibitors may prove analgesic in all of the following conditions in which LPC is elevated: rheumatoid arthritis (47), osteoarthritis (48), SCD (34), fibromyalgia (49), diabetes (50), multiple sclerosis (47), primary dysmenorrhea (51), lumbar spinal stenosis (52), and migraine (29). Additional support for TRPC5 inhibitors in migraine comes from a recent study in which Trpc5 expression was elevated in TG neurons of mice that developed pituitary adenylate cyclase activating polypeptide (PACAP)induced light aversion (53). Future studies should determine whether TRPC5 is a convergent secondary target for the G protein-coupled peptidergic signaling (CGRP and PACAP) (54) that occurs in patients with migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine pathogenesis is multifactorial. The failure of efficacy in the non-responders to current medications suggests that CGRP is not the only cause of migraine and that other neuropeptides are involved; e.g., pituitary adenylate cyclase-activating peptide (PACAP-38) works independently of CGRP or 5-HT 1B/1D/1F receptors (Kuburas et al, 2021 ; Ernstsen et al, 2022 ). In addition, CGRP-based drugs act on the periphery with low penetration across the blood-brain barrier (Edvinsson and Warfvinge, 2019 ); eg., a preclinical study reported that galcanezumab, one of the FDA-approved CGRP antibodies targeting the CGRP peptide, demonstrated limited blood-brain barrier penetration when injected peripherally into rats (Johnson et al, 2019 ).…”
Section: The Current Therapeutics For Migrainementioning
confidence: 99%